PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN PEMBERIAN HADIAH TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN PASARKLIWON KOTA SURAKARTA - Fitri Ariastuti; Suharno Suharno; Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The purpose of this study was to determine the effect of knowledge of taxation, awareness of taxpayers and gift giving to individual taxpayer compliance in paying land and building taxes. This type of research is a survey of compulsory land and building tax in Pasarkliwon District, Surakarta City. The sample of this study was 100 land and building taxpayers with purposive sampling and cluster techniques. Data collection techniques using questionnaires and literature. The data analysis technique used is multiple linear regression, t test, F test, and R2. The results of this study indicate that knowledge of taxation, awareness of taxpayers and gift giving significantly influence individual taxpayer compliance in paying land and building tax in Pasarkliwon District, Surakarta City.